STUDY ON POROSITY AND PERMEABILITY CORRELATION IN CARBONATE RESERVOIR AT BATURAJA AND KUJUNG FORMATION - Luthfi Lukman Hakim (NIM 22204001), Andri
ABSTRACT: Permeability is one of petrophysics parameter of which is proven quite difficult to determined, especially in carbonate rocks with really high degree of heterogeneity. Carbonates are rocks that have physical characteristic which is heterogeneous especially in pore and grain distribution. This research tries to apply some equations presented in literature before (K C modification) in carbonate reservoir and tries to obtain an empirical correlation that can represent permeability distribution in carbonate reservoirs. Hydraulic flow unit with facies grouping modification (re plotting FZI zone in conventional plot form) creates permeability estimation which is more accurate compared to HFU method. In this facies grouping, the equation used for fractured zone separately made from the equation used for each facies and therefore, and also the result is better than using the method of Wyllie Rose. The method generated by Willie Rose, using a correlation derived from Field T, obtains a result that can be used in Field K and shows permeability value estimation which is in the core permeability value trend.